FRI0575 PREVALENCE OF OVERWEIGHT AND OBESITY IN CHILDREN WITH JUVENILE IDIOPATHIC ARTHRITIS. (June 2019) - Sellami, Meriem; Fazaa, Alia; Miladi, Saousen; Ouenniche, Kmar; Souabni, Leila; Kassab, Selma; Chekili, Selma; Zakraoui, Leith; Abdelghani, Kawther Ben; Laatar, Ahmed
Abstract : Background: Children with juvenile idiopathic arthritis (JIA) may have an increased risk for overweight and obesity, which could be an additional risk factor for inflammatory arthritis. Objectives: The aims of this study were to determine the prevalence of overweight and obesity in children and adolescents with JIA, and to assess the association between overweight and disease parameters in this population. Methods: We assessed the weight (kg) and height (cm) according to the standard deviation score (SDS) in a cross-sectional study of JIA children. The diagnosis of JIA was based on the International League of Association of Rheumatology (ILAR) criteria. Overweight and obesity were defined by the Body Mass Index (BMI) (weight/height 2 ) matched on age and sex and in reference to the French curves. Children were classified as obese if their BMI was ≥ 95th percentile, overweight if their BMI was between the 85th and 94th percentile, and healthy weight if their BMI was between the 5th and the 84th percentiles. Functional disability was determined by the Childhood Health Assessment Questionnaire (CHAQ). Disease activity was assessed using a validated score, Juvenile Arthritis Disease Activity Score 27 (JADAS- 27). Results: Fifty-five patients (38 boys and 17 girls) with JIA were enrolled in this study. The median age was 8.5 ± 4.12 years (range 6–14). Thirty-one patients (53%) had persistant oligoarticular JIA, 15 (27%) had polyarticular JIA, 5 patients (9%) had systemic JIA, and 4 (7%) had enthesitis-related arthritis. The median disease duration was 3.2 ± 2.8 years. Twelve patients had active disease at the time of the study with a mean JADAS 27 of 6.9 ± 2.7. The mean CHAQ was 1.4 ± 0.5. Nineteen children (52.7%) had received corticosteroids during an average period of 1.7 years [0.6-3] with a mean of 10mg/day of prednisone or equivalent. The mean BMI was 14.56 ± 2.1 kg/m 2 . Twenty-two patients (40%) were overweight, 15 (27%) were obese and 18 (33%) have normal weight. Patients with normal weight, overweight and obese represented respectively 60%, 20% and 20% of systemic forms, 53%, 27% and 20% of polyarticular form, 39%, 32% and 29% of persistent oligoarticular forms, and 50%, 25% and 25% of enthesitis-related arthritis forms. Obesity was more frequent in older patients (p=0.021), with significant functional impairment (p<0.001) and with active disease (p<0.001). Only systemic JIA was more likely to be associated with overweight (p=0.031) and obesity (p=0.024). There was no relationships with other subtypes of JIA (p=0.428) or with corticosteroid treatment (p= 0.636). Conclusion: In our study, more than 60% of patients were overweight. Severe functional limitation, systemic JIA, and active disease were the most correlated parameters with obesity. Better management of the activity and functional status of the disease may reduce overweight in children with JIA. Disclosure of Interests: None declared